2023
DOI: 10.1371/journal.pone.0280396
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with tuberculosis among the mining communities in Mererani, Tanzania

Abstract: Tuberculosis (TB) is among diseases of global health importance with Sub Saharan Africa (SSA) accounting for 25% of the global TB burden. TB prevalence among miners in SSA is estimated at 3,000–7,000/100,000, which is about 3 to 10-times higher than in the general population. The study’s objective was to determine the prevalence of TB and associated risk factors among mining communities in Mererani, northern Tanzania. This was a cross-sectional study conducted from April 2019 to November 2021 involving current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Mine workers with history of suffering from TB in South Africa were reported to have reduced lung function with FEV 1 of about 180mls-lower and FVC of about 120mls-lower relative to those who never suffered TB [33]. As reported in our previous study report [15], the prevalence of TB among the mining communities in Mererani was around 7.0% which is about 18-times higher compared to the national prevalence of around 0.4% (WHO TB burden estimates 2021; https://www.who.int/teams/global-tuberculosis-programme/data). Unexpectedly, the TB burden was higher (7.9%) in the PMC compared to 6.1% for SSM.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Mine workers with history of suffering from TB in South Africa were reported to have reduced lung function with FEV 1 of about 180mls-lower and FVC of about 120mls-lower relative to those who never suffered TB [33]. As reported in our previous study report [15], the prevalence of TB among the mining communities in Mererani was around 7.0% which is about 18-times higher compared to the national prevalence of around 0.4% (WHO TB burden estimates 2021; https://www.who.int/teams/global-tuberculosis-programme/data). Unexpectedly, the TB burden was higher (7.9%) in the PMC compared to 6.1% for SSM.…”
Section: Discussionmentioning
confidence: 95%
“…We have previously described in details our study methods [15]. In brief however, we conducted a cross-sectional study in Mererani mines located in Simanjiro district, in northern Tanzania.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a total of 357 titles and abstracts, 56 studies were full-text screened and 18 eligible studies of 13 distinct populations from 10 countries included in our analysis (Fig 2) (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Of these studies, six reported on silicosis prevalence (30)(31)(32)(33)(34)(35), six on tuberculosis prevalence (33)(34)(35)(36)(37)(38), eight on dust or respirable silica exposures (30,32,(39)(40)(41)(42)(43)(44), three on spirometry findings (39,46,47) and three on respiratory symptoms (32,43,45). There was moderate agreement for title and abstract review, Cohen's kappa of 0.56 (HM) and 0.49 (BS).…”
Section: Study Selectionmentioning
confidence: 99%
“…The number of ASM enrolled in all 14 clinical studies ranged from 18 to 21,136 participants (median 441, IQR 258 -867) with an overall total of 29,562 participants. There were 14 studies from Africa (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), two studies from Asia (30,47) and two from South America (31,32). Most of the included studies were in gold (10/18) and gemstone (5/18) mining communities and were exclusively underground (10/18) or both under and above ground ASM (5/18).…”
Section: Study Selectionmentioning
confidence: 99%